Diabetes is Associated with Chronic Liver Disease and Liver Cancer in the Adult Population of Puerto Rico - Ortiz, Ana P; Romero, Carlos; Disdier, Orville; Santana, Erik; Torres, Margaret; Torres, Esther A.; Pérez, Cynthia M. (Puerto Rico Health Sciences Journal, 2011)
Objective: Diabetes mellitus (DM) has been proposed as a risk factor for both chronic liver disease (CLD) and for hepatocellular carcinoma (HCC); however, studies among Hispanics are limited. Puerto Rico (PR) has a high prevalence of DM (13%), supporting the need for a better understanding of the public health implications associated with DM in this population. We assessed the association of DM with CLD and with HCC in a population of Puerto Rican adults with health insurance. Methods: The study sample consisted of 1,040,025 individuals, aged >18 years, all covered by the government-run healthcare program in PR, in 2002. The ICD-9 codes for DM, CLD, and HCC were obtained in order to determine the prevalence of these conditions. Logistic regression models were used to determine the association of DM with CLD and with HCC, after adjusting for covariates. Results: The prevalence of DM was higher in patients with CLD (17%) and those with HCC (18%) than it was in patients without either of these conditions (8% and 7%, respectively). Among women, those with DM were significantly more likely to have CLD than were those without DM (POR: 35-49 yrs: 3.26, 95% CI = 2.12, 5.00; POR: 50-64 yrs: 2.10, 95% CI = 1.63, 2.71; POR: ≥65 yrs: 2.33, 95% CI = 1.67, 3.25). Among men, those with DM were more likely to have CLD than were those without DM; this association was significant among males aged 50-64 (POR: 1.30, 95% CI = 1.03-1.63) and those aged >65 yrs (POR: 1.94, 95% CI = 1.35-2.80). Conclusion: Consistent with other studies, we observed a strong association of DM with CLD and HCC. In order to reduce the burden of these conditions in PR, research and public health efforts should be concentrated on gaining a better understanding of these associations.